(untitled) (Indian Journal of Psychology & Education, 2026)
A high Quality of work life is very much essential to retain employees of high caliber since it has impact on human outcome, productivity, absenteeism etc. An exploratory research design has been employed with the objective of examining the gender differences in QWL among Bank and IT employees. A sample of 60 employees from State Bank of India, of which 30 male and 30 female employees and 60 employees from Accenture IT company, of which 30 male and 30 female employees have been selected through simple random sampling technique. The Quality of work life Scale developed by Dhar, Dhar and Roy (1989)is used in the study. The obtained data were analysed by using two-way ANOVA. The findings indicated that IT and Bank employees differ in their QWL. The study has important implications for managers, employers and government.